The artistry of Bald's colophon: Latin verse in an Old English medical codex. (December 2019) - Kesling, Emily
Abstract: Bald's Leechbook, the most famous of the Old English medical collections, derives its name from a colophon in Latin hexameter verse that occurs on the final folio of the collection. Previous scholarly attention to the colophon has been nearly entirely directed at discerning the relationship of two named figures ( Bald and Cild ) and their role (if any) in the creation of Bald's Leechbook. Yet given the rarity of verse colophons in Anglo-Saxon manuscripts and the unusual placement of this text at the end of a technical work in Old English, these verses also deserve study for their place within the larger genre of poetic colophons and framing texts from Anglo-Saxon England. This article examines for the first time the form of the colophon and its character as a work of Anglo-Latin verse as well as its relationship with the vernacular prefatory tradition associated with King Alfred.